Generation of ultra‐large‐bandwidth X‐ray free‐electron‐laser pulses with a transverse‐gradient undulator. (31st May 2016) - Prat, Eduard; Calvi, Marco; Reiche, Sven
Abstract : A novel, flexible yet simple method to generate gigawatt X‐ray free‐electron‐laser radiation with unprecedented spectral bandwidth above the 10% level is presented. Such broadband radiation will improve substantially the efficiency of techniques like X‐ray crystallography and spectroscopy, paving the way for outstanding progress in fields like biology and material science. Abstract : A new and simple method to generate X‐ray free‐electron‐laser radiation with unprecedented spectral bandwidth above the 10% level is presented. The broad bandwidth is achieved by sending a transversely tilted beam through a transverse‐gradient undulator. The extent of the bandwidth can easily be controlled by variation of the beam tilt or the undulator gradient. Numerical simulations confirm the validity and feasibility of this method.